miR‐181a regulates p62/SQSTM1, parkin, and protein DJ‐1 promoting mitochondrial dynamics in skeletal muscle aging - Goljanek‐Whysall, Katarzyna (Aging Cell, 2020)
One of the key mechanisms underlying skeletal muscle functional deterioration during aging is disrupted mitochondrial dynamics. Regulation of mitochondrial dynamics is essential to maintain a healthy mitochondrial population and prevent the accumulation of damaged mitochondria; however, the regulatory mechanisms are poorly understood. We demonstrated loss of mitochondrial content and disrupted mitochondrial dynamics in muscle during aging concomitant with dysregulation of miR‐181a target interactions. Using functional approaches and mito‐QC assay, we have established that miR‐181a is an endogenous regulator of mitochondrial dynamics through concerted regulation of Park2, p62/SQSTM1, and DJ‐1 in vitro. Downregulation of miR‐181a with age was associated with an accumulation of autophagy‐related proteins and abnormal mitochondria. Restoring miR‐181a levels in old mice prevented accumulation of p62, DJ‐1, and PARK2, and improved mitochondrial quality and muscle function. These results provide physiological evidence for the potential of microRNA‐based interventions for age‐related muscle atrophy and of wider significance for diseases with disrupted mitochondrial dynamics.